2016
DOI: 10.1007/s10971-016-4084-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol–water co-condensation into hydrophobic mesoporous thin films: example of a photonic ethanol vapor sensor in humid environment

Abstract: In this work, we report a new generation of solgel photonic vapor sensor based on water-repellent methylfunctionalized mesoporous silica thin films for the detection of alcohol vapors. Relative humidity, generally accountable for sensor performance deterioration, was demonstrated as a key parameter to detect and enhance sensor sensitivity concerning ethanol. The ethanol-assisted water vapor capillary condensation into hydrophobic mesopores was observed and investigated as an innovative sensing mechanism. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As proof-of-concept, we repeated the condensation experiment reported in the previous section on squared patterns but added ethanol (EtOH) in addition to water vapor. Relative vapor pressures of H 2 O and EtOH inside the chamber were controlled by bubbling dry air in a bubbler at 25 °C containing a solution of EtOH and H 2 O with 0, 1, 2.5, 5, and 10% wt% in alcohol as reported elsewhere. , The EtOH/H 2 O saturated air was “diluted” with dried air to reach a concentration of 25% in saturated vapors (as in the previous section). Condensation of EtOH/H 2 O vapors was induced by cooling down the surface at 2 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As proof-of-concept, we repeated the condensation experiment reported in the previous section on squared patterns but added ethanol (EtOH) in addition to water vapor. Relative vapor pressures of H 2 O and EtOH inside the chamber were controlled by bubbling dry air in a bubbler at 25 °C containing a solution of EtOH and H 2 O with 0, 1, 2.5, 5, and 10% wt% in alcohol as reported elsewhere. , The EtOH/H 2 O saturated air was “diluted” with dried air to reach a concentration of 25% in saturated vapors (as in the previous section). Condensation of EtOH/H 2 O vapors was induced by cooling down the surface at 2 °C.…”
Section: Resultsmentioning
confidence: 99%
“…After 1 min at room temperature, the thin film surrounded by the PDMS stamp was heated at 100 °C for 5 min on a hot plate. The PDMS stamp was then removed, and the titania thin film was finally calcinated at 450 °C for 5 min on a hot plate …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems exploiting only the change of the optical density are amongst the simplest ones, since transduction does not have to be performed spectroscopically. Simple reflected, transmitted, or guided signals can directly be exploited to detect the adsorption of EtOH, or can also be exalted using photonic phenomena to enhance even more their sensitivity to volatile organic compounds (VOCs) down to 500 ppb for instance. In these cases, highly porous and high surface area coatings such as silica xerogels were used as adsorbing matrix. However, the main issue related to detection based on adsorption-induced refractive index variation alone is its poor chemical selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the selectivity between water and alcohol within such modified xerogel coatings is not high enough to permit an accurate quantification of EtOH in realistic operating situations of detection. Nonetheless, it was recently demonstrated that a quantitative analysis of EtOH vapor can be performed in saturated humid atmosphere by coupling xerogel sensitive materials with diffraction gratings . Even if the detection limit was found at 0.07 relative EtOH vapor pressure ( P / P 0 ), which is around 3 orders of magnitude above the sensitivity needed for medical and forensic applications, it remains a proof that it is possible to optically detect ethanol in presence of a high quantity of water.…”
Section: Introductionmentioning
confidence: 99%